2008
DOI: 10.4049/jimmunol.181.5.3549
|View full text |Cite
|
Sign up to set email alerts
|

The Induction of Inflammation by Dectin-1 In Vivo Is Dependent on Myeloid Cell Programming and the Progression of Phagocytosis

Abstract: Dectin-1 is the archetypal signaling, non-Toll-like pattern recognition receptor that plays a protective role in immune defense to Candida albicans as the major leukocyte receptor for β-glucans. Dectin-1-deficiency is associated with impaired recruitment of inflammatory leukocytes and inflammatory mediator production at the site of infection. In this study, we have used mice to define the mechanisms that regulate the dectin-1-mediated inflammatory responses. Myeloid cell activation by dectin-1 is controlled by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
139
1
12

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 121 publications
(168 citation statements)
references
References 53 publications
(82 reference statements)
14
139
1
12
Order By: Relevance
“…These results are in accordance with a previous work of Rosas et al (44), which demonstrated the crucial effect of GM-CSF in cellular programming of a proinflammatory dectin-1-mediated response in macrophages. Using both curdlan and glucan microparticles, the authors showed that macrophages do not mount a significant proinflammatory cytokine response upon dectin-1 engagement, which can be dramatically boosted via GM-CSF costimulation (44). They speculated about a GM-CSF-mediated alteration of the downstream signaling components of the Syk/ CARD9 and NF-kB pathways, but the exact mechanism of action was not clarified.…”
Section: Discussionsupporting
confidence: 83%
“…These results are in accordance with a previous work of Rosas et al (44), which demonstrated the crucial effect of GM-CSF in cellular programming of a proinflammatory dectin-1-mediated response in macrophages. Using both curdlan and glucan microparticles, the authors showed that macrophages do not mount a significant proinflammatory cytokine response upon dectin-1 engagement, which can be dramatically boosted via GM-CSF costimulation (44). They speculated about a GM-CSF-mediated alteration of the downstream signaling components of the Syk/ CARD9 and NF-kB pathways, but the exact mechanism of action was not clarified.…”
Section: Discussionsupporting
confidence: 83%
“…Under our experimental conditions, the IFN-I response to Candida is highly cell-typespecific within innate immune cells, because peritoneal or BMDMs as well as neutrophils or splenic DCs challenged by Candida fail to release detectable amounts of IFN-b. Thus, our results are consistent with reports about distinct and cell-typespecific cytokine responses between BMDMs and myeloid dendritic cells (44)(45)(46), suggesting that different innate immune cells may have distinct repertoires to sense and to respond to microbial PAMPs, depending on the differentiation procedure used to obtain the cells in vitro or the host tissue environment in vivo. This may help to fine-tune the host defense and immune surveillance.…”
Section: Discussionsupporting
confidence: 81%
“…45 While thioglycollate-elicted peritoneal M did not respond to ␤-glucan, exogenous GM-CSF rendered cells producing high amount of cytokines to ␤-glucan, suggesting M differentiation in vivo might be polarized by GM-CSF and had distinct response than primary M in response to ␤-glucan stimulation. 45 Goodridge et al reported that zymosan can induce higher amount of TNF-␣ in GM-CSF-derived BMDC than in BMM (cultured by M-CSF), and ␤-glucan can only induce TNF-␣ secretion from BMDCs, but not BMM . This observation suggests that GM-CSF can activate NF-B to produce TNF-␣ induction on ␤-glucan stimulation, 46 and GM-CSF is a potent cytokine to modulate cell functions in vivo.…”
Section: Dv-induced Inflammasome Activation Is Via Clec5amentioning
confidence: 99%
“…45,46 Rosas et al found that bone marrow-derived dendritic cells (cultured by GM-CSF) produced higher amounts of cytokines than BMM (cultured by M-CSF) in response to pathogenic fungi and its derivatives. 45 While thioglycollate-elicted peritoneal M did not respond to ␤-glucan, exogenous GM-CSF rendered cells producing high amount of cytokines to ␤-glucan, suggesting M differentiation in vivo might be polarized by GM-CSF and had distinct response than primary M in response to ␤-glucan stimulation. 45 Goodridge et al reported that zymosan can induce higher amount of TNF-␣ in GM-CSF-derived BMDC than in BMM (cultured by M-CSF), and ␤-glucan can only induce TNF-␣ secretion from BMDCs, but not BMM .…”
Section: Dv-induced Inflammasome Activation Is Via Clec5amentioning
confidence: 99%